Indigenous legal forms and governance structures in renewable energy: Assessing the role and perspectives of First Nations economic development corporations - Savic, Katarina; Hoicka, Christina E. (Energy Research & Social Science, 2023)
The authors thank Alicia Campney for starting the dataset used. The Canadian Council for Aboriginal Business for their support of this research through partnership. In the literature on community energy, there has been little exploration of how legal forms affect the governance structures employed and resulting impacts to communities. In a settler colonial context like Canada, renewable energy transitions and projects will take place on or near Indigenous traditional territories. In the emerging body of knowledge around Indigenous community involvement in renewable energy the role of the Indigenous economic development corporation (EDCs), a uniquely Indigenous legal form has had little attention. Although a range of governance structures that could support renewable energy projects exist; what has not been explored are which legal forms tend to employ specific governance structures. Employing a national dataset, surveys and interviews, this study assesses the experience and involvement of Indigenous EDCs as a legal form in renewable energy projects, the governance structures EDCs employ, and how these governance structures respond to the needs for self-determination and decision-making power of Indigenous communities. The findings show that at least 26 EDCs are involved in renewable energy projects, that EDCs tend to use economic instruments, while political organizations, (e.g., Band Council), tend to use political instruments, such as impact and benefit agreements (IBAs). Interviewed and surveyed EDCs agreed that ownership of a project is more beneficial than IBAs that tend to be short lived. Although full ownership denotes control over a project, which aligns with UNDRIP, the desired level of ownership varies depending on a variety of factors, such as comfort with risk and how provincial context affects preferred ownership structures. This work was supported financially by the Smart Prosperity Institute under the Special call for proposals: Climate and Environmental Policy in the context of COVID-19. ...